In the grip of Catholic conservatism: State HIV/AIDS prevention in post-1989 Poland - Majka, Rafał (Kultura-Społeczeństwo-Edukacja, 2025)
In this article, I analyse the impact of the Catholic discourse on institutional HIV/AIDS prevention efforts in Poland. I argue that a combination of historical and political factors – including the Church’s role in the People’s Republic of Poland, the cult of John Paul II, and the signing of the Concordat–positioned the Catholic Church as a dominant political actor in post-transformation Poland, granting it considerable influence over the development of social and health policies. Concentrating on the first decade following the political and economic transformation of 1989, a period during which the Catholic Church solidified its hegemonic position, I critically evaluate the discourse surrounding HIV/AIDS prevention as presented in informational and educational materials funded by public or international resources designated for prevention initiatives. I highlight how recommendations and commentaries frequently diverge from international strategies and guidelines, reflecting a perspective more closely aligned with a conservative Catholic worldview than with an evidence-based and medically informed approach to public health.